Linear polarization low-threshold polarization laser light source capable of being treated by solution and preparation method of linear polarization low-threshold polarization laser light source

By adding specific ligands to the mixing of cesium carbonate and oleic acid and using benzoyl chloride, combining PHPS hydrolysis reaction and the design of silicon oxide sheets, a solution-treated linear polarization low-threshold polarization laser light source was prepared, solving the obstacles to traditional lasers to obtain high-polarized light output, and achieving low-threshold laser emission with multi-wavelength co-gain and high polarization degrees.

CN119799332APending Publication Date: 2025-04-11SHANDONG UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411821582.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Traditional micro/nanoscale lasers face obstacles to spontaneous emission of non-polarization characteristics when acquiring high-polarized light outputs, and existing materials have challenges in achieving multi-wavelength co-gain and stability.

Method used

By adding a specific ligand such as 4-chlorobutyric acid to the mixture of cesium carbonate and oleic acid, and using benzoyl chloride as the chlorine source, combined with the PHPS hydrolysis reaction and the design of silica oxide sheets, a solution-treated linear polarization low threshold polarization laser light source was prepared.

Benefits of technology

It realizes low excitation threshold polarization laser emission in micro-nano-stage compact size, has multi-wavelength co-gain and high polarization degree, has low threshold and stable, and is suitable for photonic integrated circuits and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119799332A_ABST
    Figure CN119799332A_ABST
Patent Text Reader

Abstract

The invention discloses a solution-treatable linear polarization low-threshold polarization laser light source and a preparation method thereof, and the preparation method comprises the following steps: mixing cesium carbonate and oleic acid, heating to 100-130 DEG C in an inert atmosphere, carrying out heat preservation for 20-40 min, after reactants are completely dissolved, heating to 140-160 DEG C, and carrying out heat preservation for 10-30 min to obtain a precursor solution A; mixing the precursor solution A, erbium acetate, yttrium acetate, bismuth acetate, silver acetate, sodium oleate, octadecene, 4-chlorobutyric acid and oleylamine according to a set proportion, standing for a set time in an inert atmosphere, stirring and heating to 90-110 DEG C, preserving heat for 0.5-1.5 h, heating to 130-150 DEG C after reactants are completely dissolved, injecting benzoyl chloride, reacting for 1-5 minutes, cooling, and stopping reaction; carrying out solid-liquid separation on the obtained mixed solution, cleaning the quantum dots, then dispersing the quantum dots in a dispersing solvent, adding PHPS into the dispersing solvent, and carrying out ultrasonic mixing; and after the PHPS is fully hydrolyzed, coating a silicon oxide sheet with the solution to prepare a film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of quantum dot material laser emission, and in particular relates to a solution-processable linearly polarized low-threshold polarized laser light source and a preparation method thereof. Background Art

[0002] The statements herein merely provide background information related to the present invention and do not necessarily constitute prior art.

[0003] Linearly polarized micro / nano lasers, with their potential miniaturization characteristics and low-power coherent light source advantages, have stimulated widespread research interest in many fields such as free-space optical communication links, exploration of nonlinear optical effects, high-precision spectral analysis, advanced sensing technology, and compact laser display systems. This type of laser can achieve simultaneous access and manipulation of multi-wavelength lasers in a compact space, laying a solid foundation for advancing cutting-edge scientific and technological fields such as efficient optical information processing, high-density optical data storage, and multi-modal biochemical sensing. However, traditional lasers usually rely on highly polarized seed light sources to generate polarized light, and at the micro / nano scale, the non-polarization characteristics of spontaneous emission have become the main obstacle to directly obtaining highly polarized laser output. To solve this problem, researchers have tried to construct polarized micro / nano lasers through fine-tuning of material morphology and innovative design of molecular structure, but these methods are often cumbersome and difficult to adapt to the needs of large-scale industrial production.

[0004] Recently, metal halide perovskite materials have attracted much attention due to their excellent optical properties, especially in achieving polarized luminescence and specific wavelength lasers in composite films. However, the material faces challenges in achieving multi-wavelength co-gain at the same time, coupled with its potential toxicity and chemical stability issues, which limits its application potential in a wider range of fields. Summary of the invention

[0005] In view of the shortcomings of the prior art, the object of the present invention is to provide a solution-processable linearly polarized low-threshold polarized laser light source and a preparation method thereof.

[0006] In order to achieve the above object, the present invention is implemented through the following technical solutions:

[0007] In a first aspect, the present invention provides a method for preparing a solution-processable linearly polarized low-threshold polarized laser light source, comprising the following steps:

[0008] Mix cesium carbonate and oleic acid, heat to 100-130°C in an inert atmosphere, keep warm for 20-40 minutes, and after the reactants are completely dissolved, heat to 140-160°C and keep warm for 10-30 minutes to obtain a precursor solution A;

[0009] Precursor solution A, erbium acetate, yttrium acetate, bismuth acetate, silver acetate, sodium oleate, octadecene, 4-chlorobutyric acid and oleylamine are mixed in a set ratio, left to stand for a set time in an inert atmosphere, stirred and heated to 90-110°C, kept warm for 0.5-1.5h, and after the reactants are completely dissolved, the temperature is raised to 130-150°C, benzoyl chloride is injected, reacted for 1-5min, cooled, and the reaction is stopped;

[0010] The obtained mixed solution is solid-liquid separated, the quantum dots are washed, and then the quantum dots are dispersed in a dispersion solvent, PHPS (perhydropolysilazane) is added thereto, and ultrasonic mixing is performed;

[0011] When PHPS is fully hydrolyzed, the solution is coated on a silicon oxide sheet to prepare a film.

[0012] The purpose of reacting cesium carbonate with oleic acid to generate cesium oleate, i.e., precursor solution A, is that cesium oleate has better solubility in certain solvents than cesium carbonate. This helps to ensure that the reactants can be evenly mixed during the synthesis process, thereby improving the efficiency of the reaction and the quality of the product.

[0013] Unlike other patent documents, 4-chlorobutyric acid is added as one of the ligands of perovskite quantum dots because the carbon chain of the ligand is shorter, which enables it to bind more effectively to the surface of perovskite quantum dots and form a more stable structure. Short-chain ligands can reduce the steric hindrance on the surface of quantum dots, thereby enhancing the interaction between the ligand and the quantum dots. In subsequent applications, it can more effectively prevent the ligand from falling off and maintain the stability and dispersibility of quantum dots.

[0014] Benzoyl chloride is a chlorine source, which is crucial for the formation of the crystal structure of perovskite quantum dots, because halide ions are an important component of the perovskite structure. By adding benzoyl chloride, it can ensure that there are enough halide ions in the reaction system, which is conducive to the formation and stability of perovskite quantum dots.

[0015] As the substrate of optical film, silicon oxide flakes can ensure that the film layer has high light transmittance and transparency.

[0016] In some embodiments, the molar ratio of cesium carbonate, oleic acid, erbium acetate, yttrium acetate, bismuth acetate, silver acetate, sodium oleate, octadecene, 4-chlorobutyric acid and oleylamine is 0.2-0.3:3.5-4.5:0.01-1.0:0.1-0.2:0.002-0.003:0.08-0.1:0.1-0.15:24-26:13-15:2-3.

[0017] Preferably, the molar ratio of cesium carbonate, oleic acid, erbium acetate, yttrium acetate, bismuth acetate, silver acetate, sodium oleate, octadecene, 4-chlorobutyric acid and oleylamine is 0.25:4.0:0-1.0:0.1-0.2:0.0025:0.08:0.12:24.75:13.16:2.34.

[0018] In some embodiments, after the substances are mixed, they are allowed to stand in an inert atmosphere for 10-30 minutes to remove the residual oxygen in the device to oxidize oleylamine during the experiment.

[0019] In some embodiments, benzoyl chloride is injected, and after reacting for 1-5 minutes, ice water is used to cool the temperature to stop the quantum dot synthesis reaction.

[0020] In some embodiments, the dispersing solvent is cyclohexane.

[0021] In some embodiments, the method further comprises focusing a picosecond pulse laser having a wavelength of 355 nm on the erbium ion-doped Cs2Ag 0.4 Na 0.6 Y 0.98 Bi 0.02 Steps on the surface of Cl6@SiO2 thin films.

[0022] Preferably, the pulse width of the picosecond pulse laser is 10 ps and the repetition frequency is 48 MHz.

[0023] In some embodiments, after PHPS is fully hydrolyzed, the solution is spin-coated on a silicon oxide wafer to prepare a film. The silicon oxide wafer is chemically stable and does not easily react with a variety of chemicals, thereby ensuring the stability of the coating solution and the integrity of the film layer.

[0024] Preferably, air circulation is maintained during the hydrolysis of PHPS to ensure that water molecules in the air participate in the process of hydrolysis of PHPS to generate silicon oxide.

[0025] Preferably, the spin coating speed is 3500-4500 rpm, and the spin coating time is 70-100 s.

[0026] In a second aspect, the present invention provides a solution-processable linearly polarized low-threshold polarized laser light source prepared by the preparation method.

[0027] The beneficial effects achieved by one or more embodiments of the present invention are as follows:

[0028] The uniqueness of the present invention lies in the ingenious combination of the concentration control of the quantum dot solution and PHPS (a specific treatment process). By precisely controlling the thickness of the film and the design of the silicon oxide cavity, the Si-N bond in PHPS is very easy to undergo a hydrolysis reaction. The hydrolysis reaction is usually carried out in two steps: first, the Si-N bond is hydrolyzed to generate silanol (Si-OH) and release small molecules of NH3; then, the generated Si-OH undergoes a condensation reaction to form a Si-O-Si structure. The release of nitrogen produces small bubbles in the film, and the cavity lays a solid physical foundation for laser emission. Furthermore, the present invention uses a high concentration of rare earth elements to replace the optically inert rare earth element Y in the double perovskite quantum dots (Y ions are selected instead of traditional In ions because Y ions with rare earth optical inertness are more conducive to being replaced by rare earth element Er ions), and through self-limited energy transfer to the rare earth energy level, and using the special electron cloud arrangement and asymmetric structure of double perovskites, low excitation threshold polarized laser emission at a compact micro-nano size is achieved, which has extremely high application value.

[0029] The present invention provides a method for preparing a silicon oxide-coated quantum dot film to generate a linearly polarized low-threshold laser. 3+ Cs2Ag 0.4 Na 0.6 Y 0.98 Bi 0.02 Cl6 double perovskite quantum dots are embedded in an inhomogeneous silica structure, which exhibits linearly polarized multi-wavelength laser emission in the visible and near-infrared wavelength ranges. The structure provides a closed-loop path through random scattering, thereby supporting multiple optical feedbacks and random laser generation. The multi-wavelength polarized laser exhibits an ultra-low threshold (11.69pJ at 533nm, 12.64pJ at 559nm, 13.22pJ at 657nm, and 12.21pJ at 808nm), and the maximum polarization degree reaches 0.89. With its advantages of miniaturization, ultra-low threshold, and integrated adaptability, it provides a promising light source for future photonic integrated circuits for large-capacity optical devices.

[0030] The solution-processable method makes the preparation of polarized laser devices more flexible; 4-chlorobutyric acid is added during the synthesis process to enhance the stability of the material. Rare earth doping makes the laser threshold lower. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0032] Figure 1 This is a powder X-ray diffraction pattern of the erbium ion heavily doped quantum dots described in Examples 1-6 of the present invention.

[0033] Figure 2 This is the transmission electron microscope diffraction pattern of the erbium ion heavily doped quantum dots described in Examples 1-6 of the present invention.

[0034] Figure 3 The photoluminescence images of the bait ion heavily doped quantum dots described in Examples 1-6 of the present invention have an excitation wavelength of 365 nm, wherein a is a photoluminescence spectrum of different doping amounts; and b is a comparison diagram of the self-limiting state intensities of different doping amounts.

[0035] Figure 4 This is the polarized photoluminescence image of the bait ion heavily doped quantum dots described in Examples 1-6 of the present invention, with an excitation wavelength of 365 nm, wherein a is 0 mmol; b is 0.1 mmol; c is 0.2 mmol; d is 0.4 mmol; e is 0.8 mmol; and f is 1.0 mmol.

[0036] Figure 5 This is a scanning electron microscope image of the cross-section of the silicon oxide-coated erbium ion heavily doped quantum dot film described in Examples 7-8 of the present invention, wherein a represents the film thickness of 153.3 nm, and b represents the film thickness of 96.58 nm.

[0037] Figure 6 These are test diagrams of laser emission of the erbium ion heavily doped quantum dot film at different powers as described in Examples 9-13 of the present invention, wherein a is the laser emission spectrum of the erbium ion heavily doped quantum dot film at different powers; and b is the test site diagram.

[0038] Figure 7 H described in Examples 9-13 of the present invention 11 / 2 → 4 I 15 / 2 (533nm), 4 S 3 / 2 → 4 I 15 / 2 (559nm), 4 F 9 / 2 → 4 I 15 / 2 (657nm)and 4 I 9 / 2 → 4 I 15 / 2 The intensity and line width of the (808nm) transition peak vary with pump intensity.

[0039] Figure 8 The photoluminescence spectra at different angles described in Example 9 of the present invention. DETAILED DESCRIPTION

[0040] It should be noted that the following detailed descriptions are illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0041] The present invention will be further described below in conjunction with the embodiments.

[0042] Embodiment 1:

[0043] (1) Preparation of precursor solution

[0044] 830 mg of cesium carbonate and 10 ml of oleic acid were placed in a four-necked flask, and the flask was allowed to stand under a nitrogen atmosphere to expel the air. The magnetic stirring and heating device were turned on to raise the temperature to 120°C and keep it for 30 minutes. After the reactants were completely dissolved, the temperature was raised to 150°C and kept for 20 minutes to obtain cesium oleate precursor solution A.

[0045] (2) 1.0 ml of solution A, 0.10 mmol of yttrium acetate, 0.0025 mmol of bismuth acetate, 0.08 mmol of silver acetate, 0.12 mmol of sodium oleate, 5.0 ml of octadecene, 2.0 ml of 4-chlorobutyric acid, and 0.5 ml of oleylamine were placed in a four-necked flask, and finally 0.4 mmol of erbium acetate was added to the flask. The mixture was allowed to stand for 20 min under a nitrogen atmosphere, and the magnetic stirring and heating device were turned on. The mixture was then heated to 100 °C and maintained at this temperature for 1 hour until the reactants were completely dissolved.

[0046] (3) After the reactants were completely dissolved, the solution was quickly heated to 140°C, and then 0.3 ml of benzoyl chloride was injected. After 2 min, the solution was cooled with ice water to stop the reaction.

[0047] (4) Add cyclohexane and ethyl acetate in a volume ratio of 2:1 to the mixture, centrifuge at 8000 rpm for 10 min, and discard the supernatant after precipitation; repeat the addition of mixed reagents and centrifugation, discard the supernatant, obtain quantum dots, and disperse the quantum dots in 10 ml of cyclohexane.

[0048] (5) Using cyclohexane as a dispersing solvent, the high-concentration quantum dot solution and the PHPS solution are thoroughly mixed by ultrasonication, wherein the quantum dot solubility is 0.1 mol / L, and the volume ratio of the quantum dot solution to the PHPS solution is 8:1.

[0049] Embodiment 2:

[0050] Compared with Example 1, most of them are the same, except that in step 2), 1.0 ml of solution A, 0.20 mmol of yttrium acetate, 0.0025 mmol of bismuth acetate, 0.08 mmol of silver acetate, 0.12 mmol of sodium oleate, 5.0 ml of octadecene, 2.0 ml of 4-chlorobutyric acid, and 0.5 ml of oleylamine are placed in a four-necked flask, allowed to stand for 20 min under a nitrogen atmosphere, the magnetic stirring and heating device are turned on, and then the mixture is heated to 100 ° C. and maintained at this temperature for 1 hour.

[0051] Embodiment 3:

[0052] Compared with Example 1, most of them are the same, except that in step 2), 1.0 ml of solution A, 0.10 mmol of yttrium acetate, 0.0025 mmol of bismuth acetate, 0.08 mmol of silver acetate, 0.12 mmol of sodium oleate, 5.0 ml of octadecene, 2.0 ml of 4-chlorobutyric acid, and 0.5 ml of oleylamine are charged into a four-necked flask, and finally 0.10 mmol of erbium acetate is added into the flask, and the mixture is allowed to stand for 20 min under a nitrogen atmosphere, and the magnetic stirring and heating device are turned on, and then the mixture is heated to 100 ° C. and maintained at this temperature for 1 hour.

[0053] Embodiment 4:

[0054] Compared with Example 1, most of them are the same, except that in step 2), 1.0 ml of solution A, 0.10 mmol of yttrium acetate, 0.0025 mmol of bismuth acetate, 0.08 mmol of silver acetate, 0.12 mmol of sodium oleate, 5.0 ml of octadecene, 2.0 ml of 4-chlorobutyric acid, and 0.5 ml of oleylamine are charged into a four-necked flask, and finally 0.20 mmol of erbium acetate is added into the flask and allowed to stand for 20 min under a nitrogen atmosphere, magnetic stirring and heating device are turned on, and then the mixture is heated to 100 ° C. and maintained at this temperature for 1 hour.

[0055] Embodiment 5:

[0056] Compared with Example 1, most of them are the same, except that in step 2), 1.0 ml of solution A, 0.10 mmol of yttrium acetate, 0.0025 mmol of bismuth acetate, 0.08 mmol of silver acetate, 0.12 mmol of sodium oleate, 5.0 ml of octadecene, 2.0 ml of 4-chlorobutyric acid, and 0.5 ml of oleylamine are charged into a four-necked flask, and finally 0.80 mmol of erbium acetate is added into the flask and allowed to stand for 20 min under a nitrogen atmosphere, magnetic stirring and heating device are turned on, and then the mixture is heated to 100 ° C. and maintained at this temperature for 1 hour.

[0057] Embodiment 6:

[0058] Compared with Example 1, most of them are the same, except that in step 2), 1.0 ml of solution A, 0.10 mmol of yttrium acetate, 0.0025 mmol of bismuth acetate, 0.08 mmol of silver acetate, 0.12 mmol of sodium oleate, 5.0 ml of octadecene, 2.0 ml of 4-chlorobutyric acid, and 0.5 ml of oleylamine are charged into a four-necked flask, and finally 1.00 mmol of erbium acetate is added into the flask and allowed to stand for 20 min under a nitrogen atmosphere, magnetic stirring and heating device are turned on, and then the mixture is heated to 100° C. and maintained at this temperature for 1 hour.

[0059] The powder X-ray diffraction patterns of the erbium ion heavily doped quantum dots of Examples 1-6 are shown in Figure 1 ,pass Figure 1 It can be seen that the quantum dots The crystal phase did not change, proving that the quantum dots still maintained a cubic structure after being doped with bait ions.

[0060] The transmission electron microscope diffraction patterns of the erbium ion heavily doped quantum dots of Examples 1-6 are as follows: Figure 2 ,have Figure 2 It can be seen that the size of quantum dots synthesized by hot injection is around 13-15nm.

[0061] The photoluminescence images of the erbium ion heavily doped quantum dots of Examples 1-6 are shown in FIG. Figure 3 As shown by Figure 3 As can be seen in figure a, when the doping concentration of the bait ion is 0 mmol, there is only one broad self-limited emission in the photoluminescence spectrum. As the doping concentration of the bait ion increases, the intensity of the characteristic emission peak of the bait ion at the self-limited state increases in the normalized spectrum. When the doping concentration of the bait ion is greater than 0.40 mmol, the concentration of the characteristic peak gradually decreases. Figure 3 Figure b in the middle shows the self-limiting state intensity at different doping levels. It can be seen that with the doping of bait ions, the intensity of the self-limiting state emission peak gradually decreases, which is caused by energy transfer; and when the bait ion doping concentration is greater than 0.40mmol, the bait ion characteristic peak intensity decreases and the self-limiting state energy also decreases. This is because the high concentration of bait ions doped causes defects in the overall lattice, resulting in the generation of non-radiative transitions.

[0062] The polarized photoluminescence images of the erbium ion heavily doped quantum dots described in Examples 1-6 are shown in FIG. Figure 4 As shown in the figure, it can be seen that Cs2Ag 0.4 Na 0.6 Y 0.98 Bi 0.02 Cl6 double perovskite quantum dots exhibit polarization characteristics. When doped with erbium ions, the polarization degree of the original self-limited emission peak remains unchanged, and the characteristic fluorescence peak of erbium ions is also polarized.

[0063] Embodiment 7:

[0064] (1) Preparation of precursor solution

[0065] 830 mg of cesium carbonate and 10 ml of oleic acid were placed in a four-necked flask, and the flask was allowed to stand under a nitrogen atmosphere to expel the air. The magnetic stirring and heating device were turned on to raise the temperature to 120°C and keep it for 30 minutes. After the reactants were completely dissolved, the temperature was raised to 150°C and kept for 20 minutes to obtain cesium oleate precursor solution A.

[0066] (2) 1.0 ml of precursor solution A, 0.40 mmol of yttrium acetate, 0.0025 mmol of bismuth acetate, 0.08 mmol of silver acetate, 0.12 mmol of sodium oleate, 0.3 ml of benzoyl chloride, 5.0 ml of octadecene, 2.0 ml of 4-chlorobutyric acid, and 0.5 ml of oleylamine were placed in a four-necked flask, and finally 0.4 mmol of erbium acetate was added to the flask. The mixture was allowed to stand for 20 min under a nitrogen atmosphere, and the magnetic stirring and heating device were turned on. The mixture was then heated to 100 °C and maintained at this temperature for 1 hour until the reactants were completely dissolved.

[0067] (3) After the reactants were completely dissolved, the solution was quickly heated to 140°C, and then 0.3 ml of benzoyl chloride was injected. After 2 min, the solution was cooled with ice water to stop the reaction.

[0068] (4) Add cyclohexane and ethyl acetate in a volume ratio of 2:1 to the mixture, centrifuge at 8000 rpm for 10 min, and discard the supernatant after precipitation; repeat the addition of mixed reagents and centrifugation, discard the supernatant, obtain quantum dots, and disperse the quantum dots in 10 ml of cyclohexane.

[0069] (5) Using cyclohexane as a dispersing solvent, the high-concentration quantum dot solution and the PHPS solution are thoroughly mixed by ultrasonication, wherein the quantum dot solubility is 0.1 mol / L, and the volume ratio of the quantum dot solution to the PHPS solution is 8:1.

[0070] (6) After PHPS was fully hydrolyzed, it was prepared as a film on a transparent silicon oxide wafer by spin coating at a speed of 4000 rpm for 90 s.

[0071] Embodiment 8:

[0072] Compared with Example 7, most of the steps are the same, except that in step 6), after PHPS is fully hydrolyzed, a film is prepared on a transparent silicon oxide wafer by spin coating at a speed of 2000 rpm for 90 seconds.

[0073] Different spinning speeds result in different film thicknesses. When the speed is 2000 rpm, the film thickness is 153.3 nm; when the speed is 4000 rpm, the film thickness is 96.58 nm. Figure 5 shown.

[0074] Embodiment 9:

[0075] (1) Preparation of precursor solution

[0076] 830 mg of cesium carbonate and 10 ml of oleic acid were placed in a four-necked flask, and the flask was allowed to stand under a nitrogen atmosphere to expel the air. The magnetic stirring and heating device were turned on to raise the temperature to 120°C and keep it for 30 minutes. After the reactants were completely dissolved, the temperature was raised to 150°C and kept for 20 minutes to obtain cesium oleate precursor solution A.

[0077] (2) 1.0 ml of precursor solution A, 0.40 mmol of yttrium acetate, 0.0025 mmol of bismuth acetate, 0.08 mmol of silver acetate, 0.12 mmol of sodium oleate, 0.3 ml of benzoyl chloride, 5.0 ml of octadecene, 2.0 ml of 4-chlorobutyric acid, and 0.5 ml of oleylamine were placed in a four-necked flask, and finally 0.4 mmol of erbium acetate was added to the flask. The mixture was allowed to stand for 20 min under a nitrogen atmosphere, and the magnetic stirring and heating device were turned on. The mixture was then heated to 100 °C and maintained at this temperature for 1 hour until the reactants were completely dissolved.

[0078] (3) After the reactants were completely dissolved, the solution was quickly heated to 140°C, and then 0.3 ml of benzoyl chloride was injected. After 2 min, the solution was cooled with ice water to stop the reaction.

[0079] (4) Add cyclohexane and ethyl acetate in a volume ratio of 2:1 to the mixture, centrifuge at 8000 rpm for 10 min, and discard the supernatant after precipitation; repeat the addition of mixed reagents and centrifugation, discard the supernatant, obtain quantum dots, and disperse the quantum dots in 10 ml of cyclohexane.

[0080] (5) Using cyclohexane as a dispersing solvent, the high-concentration quantum dot solution and the PHPS solution are thoroughly mixed by ultrasonication, wherein the quantum dot solubility is 0.1 mol / L, and the volume ratio of the quantum dot solution to the PHPS solution is 8:1.

[0081] (6) After PHPS was fully hydrolyzed, it was prepared as a film on a transparent silicon oxide wafer by spin coating at a speed of 4000 rpm for 90 s.

[0082] (7) Focus the picosecond pulse laser with a wavelength of 355 nm on the Bi:Cs2Ag doped with erbium ions 0.4 Na 0.6 YCl6@SiO2 film surface (pulse width is 10ps, repetition frequency is 48MHz), where the power is 2000μW.

[0083] Embodiment 10:

[0084] Compared with Example 9, most of the steps are the same, except that step 7) a picosecond pulse laser with a wavelength of 355 nm is focused on the Bi:Cs2Ag doped with erbium ions. 0.4 Na 0.6 YCl6@SiO2 film surface (pulse width is 10ps, repetition frequency is 48MHz), with a power of 50μW.

[0085] Embodiment 11:

[0086] Compared with Example 9, most of the steps are the same, except that step 7) a picosecond pulse laser with a wavelength of 355 nm is focused on the Bi:Cs2Ag doped with erbium ions. 0.4 Na 0.6 YCl6@SiO2 film surface (pulse width is 10ps, repetition frequency is 48MHz), where the power is 200μW.

[0087] Embodiment 12:

[0088] Compared with Example 9, most of the steps are the same, except that step 7) a picosecond pulse laser with a wavelength of 355 nm is focused on the Bi:Cs2Ag doped with erbium ions. 0.4 Na 0.6 YCl6@SiO2 film surface (pulse width is 10ps, repetition frequency is 48MHz), where the power is 500μW.

[0089] Embodiment 13:

[0090] Compared with Example 9, most of the steps are the same, except that step 7) a picosecond pulse laser with a wavelength of 355 nm is focused on the Bi:Cs2Ag doped with erbium ions. 0.4 Na 0.6 YCl6@SiO2 film surface (pulse width is 10ps, repetition frequency is 48MHz), where the power is 1000μW.

[0091] The laser emission test diagrams of the erbium ion heavily doped quantum dot thin film at different powers described in Examples 9-13 are as follows: Figure 6 shown.

[0092] H described in Examples 9-13 11 / 2 → 4 I 15 / 2 (533nm), 4 S 3 / 2 → 4 I 15 / 2 (559nm), 4 F 9 / 2 → 4 I 15 / 2 (657nm)and 4 I9 / 2 → 4 I 15 / 2 The intensity and line width of the transition peak (808nm) vary with the pump intensity. Figure 7 As shown, the calculated multi-wavelength polarized laser exhibits an ultra-low threshold value of 11.69 pJ at 533 nm, 12.64 pJ at 559 nm, 13.22 pJ at 657 nm, and 12.21 pJ at 808 nm.

[0093] The photoluminescence spectra at different angles described in Example 9 are as follows: Figure 8 shown.

[0094] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a solution-processable linearly polarized low-threshold polarized laser light source, characterized in that: The steps include: Mix cesium carbonate and oleic acid, heat to 100-130°C in an inert atmosphere, keep warm for 20-40 minutes, and after the reactants are completely dissolved, heat to 140-160°C and keep warm for 10-30 minutes to obtain a precursor solution A; Precursor solution A, erbium acetate, yttrium acetate, bismuth acetate, silver acetate, sodium oleate, octadecene, 4-chlorobutyric acid and oleylamine are mixed in a set ratio, left to stand for a set time in an inert atmosphere, stirred and heated to 90-110°C, kept warm for 0.5-1.5h, and after the reactants are completely dissolved, the temperature is raised to 130-150°C, benzoyl chloride is injected, reacted for 1-5min, cooled, and the reaction is stopped; The obtained mixed solution is solid-liquid separated, the quantum dots are washed, and then the quantum dots are dispersed in a dispersion solvent, PHPS is added thereto, and ultrasonic mixing is performed; When PHPS is fully hydrolyzed, the solution is coated on a silicon oxide sheet to prepare a film.

2. The method for preparing a solution-processable linearly polarized low-threshold polarized laser light source according to claim 1, characterized in that: The molar ratio of cesium carbonate, oleic acid, erbium acetate, yttrium acetate, bismuth acetate, silver acetate, sodium oleate, octadecene, 4-chlorobutyric acid and oleylamine is 0.2-0.3:3.5-4.5:0.01-1.0:0.1-0.2:0.002-0.003:0.08-0.1:0.1-0.15:24-26:13-15:2-3; Preferably, the molar ratio of cesium carbonate, oleic acid, erbium acetate, yttrium acetate, bismuth acetate, silver acetate, sodium oleate, octadecene, 4-chlorobutyric acid and oleylamine is 0.25:4.0:0-1.0:0.1-0.2:0.0025:0.08:0.12:24.75:13.16:2.

34.

3. The method for preparing a solution-processable linearly polarized low-threshold polarized laser light source according to claim 1, characterized in that: After mixing all the materials, let them stand in an inert atmosphere for 10-30 minutes.

4. The method for preparing a solution-processable linearly polarized low-threshold polarized laser light source according to claim 1, characterized in that: Inject benzoyl chloride, react for 1-5 minutes, and then cool with ice water.

5. The method for preparing a solution-processable linearly polarized low-threshold polarized laser light source according to claim 1, characterized in that: The dispersing solvent is cyclohexane.

6. The method for preparing a solution-processable linearly polarized low-threshold polarized laser light source according to claim 1, characterized in that: The invention also includes focusing a picosecond pulse laser with a wavelength of 355 nm on the erbium ion-doped Cs2Ag 0.4 Na 0.6 Y 0.98 Bi 0.02 Steps on the surface of Cl6@SiO2 film; Preferably, the pulse width of the picosecond pulse laser is 10 ps and the repetition frequency is 48 MHz.

7. The method for preparing a solution-processable linearly polarized low-threshold polarized laser light source according to claim 1, characterized in that: When PHPS is fully hydrolyzed, the solution is spin-coated on a silicon oxide wafer to prepare a film.

8. The method for preparing a solution-processable linearly polarized low-threshold polarized laser light source according to claim 1, characterized in that: During the PHPS hydrolysis process, keep the air circulating.

9. The method for preparing a solution-processable linearly polarized low-threshold polarized laser light source according to claim 1, characterized in that: The spin coating speed is 3500-4500 rpm, and the spin coating time is 70-100 s.

10. A solution-processable linearly polarized low-threshold polarized laser light source, characterized in that: Prepared by the preparation method described in any one of claims 1 to 9.

Citation Information

Cited By

  • Polarization miniature LED device capable of adjusting light emitting color and preparation method thereof

    CN119816161A